2023
DOI: 10.2147/dddt.s315359
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Utility of Osilodrostat in Cushing’s Disease: Review of Currently Available Literature

Abstract: Cushing's disease (CD) is caused by endogenous hypercortisolism as a result of adrenocorticotropin (ACTH) secretion from a pituitary tumor. The condition is associated with multiple comorbidities and increased mortality. First-line therapy for CD is pituitary surgery, performed by an experienced pituitary neurosurgeon. Hypercortisolism may often persist or recur after initial surgery. Patients with persistent or recurrent CD will generally benefit from medical therapy, often administered to patients who underw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…[ 19 ] Simultaneous use of osilodrostat and oral contraceptives does not affect their half-life and metabolism. [ 20 ] Based on the available clinical data, the recommended dose of osilodrostat initiation to control hypercortisolism in CS is 2 mg twice daily, which is gradually up-titrated over several weeks with the aim to normalize 24-hour UFC on patients, without precipitating clinical and biochemical features of hypocortisolism like asthenia and hyperkalaemia among others. Commonly used maintenance dose is 4–14 mg twice daily with a maximum dose of 30 mg twice daily.…”
Section: Discussionmentioning
confidence: 99%
“…[ 19 ] Simultaneous use of osilodrostat and oral contraceptives does not affect their half-life and metabolism. [ 20 ] Based on the available clinical data, the recommended dose of osilodrostat initiation to control hypercortisolism in CS is 2 mg twice daily, which is gradually up-titrated over several weeks with the aim to normalize 24-hour UFC on patients, without precipitating clinical and biochemical features of hypocortisolism like asthenia and hyperkalaemia among others. Commonly used maintenance dose is 4–14 mg twice daily with a maximum dose of 30 mg twice daily.…”
Section: Discussionmentioning
confidence: 99%
“…It was soon discovered, nevertheless, that Osilodrostat also inhibits 11-beta hydroxylase (CYP11B1), which lowers serum cortisol levels. 7 Perhaps due to decreased cortisol levels, there were many reasons for the administration of Osilodrostat; thus, what was needed for the resistance was a selective aldosterone inhibitor, which was conceived and licensed by CinCor Pharma Inc. Baxdrostat, a drug in phase 2 clinical trials, exemplifies exceptional selective suppression of aldosterone synthase without blocking 11-beta hydroxylase. 8 Animal model studies conducted on cynomolgus monkeys suggested that this drug inhibits the production of aldosterone without influencing the increase in cortisol caused by adrenocorticotropic hormone.…”
mentioning
confidence: 99%
“…It was soon discovered, nevertheless, that Osilodrostat also inhibits 11‐beta hydroxylase (CYP11B1), which lowers serum cortisol levels. 7 …”
mentioning
confidence: 99%